STRATEGI PENGEMBANGAN USAHA INDUSTRI KERAJINAN BAMBU BATIK UD. BETRIS DI KELURAHAN MERAS KECAMATAN BUNAKEN KOTA MANADO - Julia ., Lendombela; Melsje Y. Memah; Agnes E. Loho (AGRI-SOSIOEKONOMI, 2018)
This study aims to identify internal factors and external factors of UD Betris, as well as to determine the strategy for developing the business of bamboo batik handicraft industry UD Betris. Betris in Meras Village. This research was conducted from April to June 2018. The data used were primary data and secondary data. Primary data is obtained through observation and interviews which are divided into two parties, namely internal parties (business owners and labor) and external parties (local government and consumers) with 8 (eight) respondents. Meanwhile, secondary data was obtained from literature studies. Analysis of the data used is by using a SWOT analysis. The results showed that internal factors include: raw materials, quality of raw materials, price of raw materials, product uniqueness, business spirit and craftsman skills, product prices, product durability and quality, not having financial records, traditional production equipment, product arrangement that has not been arranged neat, promotion is not efficient, does not have a special place of business, and there is no parking space. external factors include: high market opportunities, government support, opportunities for training, opportunities to participate in exhibitions, plastic substitute goods, interest in business successors, and the existence of competitors using modern production tools. Based on the SWOT diagram, the chosen strategy is a combination of SO, namely: 1) Maintaining product quality and continuing to develop products by innovating to create bamboo handicraft products with new designs. 2) Continue to work with the government and related agencies to develop and expand marketing areas so that products are better known to local and foreign communities through training and exhibition events. *jnkd*.